An Illinois sampler : teaching and research on the prairie - Winkelmes, Mary-Ann, 1964-; Burton, Antoinette M., 1961-; Mays, Kyle T., 1987- (University of Illinois Press, 2014)
"Major research universities expect faculty to conduct significant research but also to excel as teachers. Too often those outside the classroom assume that these two functions have little in common when in fact the best teachers conduct exciting and innovative research that provides students the opportunity to learn by doing. An Illinois Sampler presents personal accounts from faculty members at the University of Illinois at Urbana-Champaign and other contributors, about their research and how it enriches and energizes their teaching. Contributors from the humanities, engineering, social and natural sciences, and other disciplines explore how ideas, methods, and materials merge to lead their students down life-changing paths to creativity, discovery, and solutions. As faculty introduce their classes to work conducted from the Illinois prairie to the farms of Africa, from densely populated cities to dense computer coding, they generate an atmosphere where research, teaching, and learning thrive inside a feedback loop of education across disciplines. Aimed at alumni and prospective students interested in the university's ongoing mission, as well as current faculty and students wishing to stay up to date on the diverse work being done around them, An Illinois Sampler offers a rare glimpse into the impact of cutting-edge research on undergraduate education in a rapidly changing world. The book also showcases the best, the most ambitious, and the most effective teaching practices developed and nurtured at one of the world's premier research universities."--Publisher
"Presents personal accounts from faculty members at the University of Illinois, Urbana-Champaign, about their research and how it enriches and energizes their teaching."--Front jacket flap.
Keywords: College teaching.; Education, Higher -- Research.; Enseignement supérieur -- Recherche.; EDUCATION -- Higher.; EDUCATION -- Essays.; College teaching; Education, Higher -- Research